Price stability and balanced public accounts as a condition for sustainable development - CIAMPI, C.A. (PSL Quarterly Review, 2013)
The article illustrates Italy's economic recovery as part of a process of renewal involving the institutions, every area of the economy and Italian society as a whole. After the turning point in 1992, a general consensus emerged that European integration was necessary and fully consistent with the national interest. In this context, the three components of economic policy - budgetary policy, incomes policy, monetary policy - are working in tandem, ensuring stability, the essential condition from any lasting and sustainable growth. Thus inflation has now been beaten; the balance of payments on current account has recorded increasing and substantial surpluses, and there has been a huge reduction in the budget deficit, with a large primary surplus. The sustainability of these results is ensured by the implementation of structural reforms: tax reform, reform of central government budget, reform of the civil service, pensions reform and reform of Italy’s commercial system. JEL Codes: E65, E63, F15